PENGARUH FAKTOR PSIKOLOGIS TERHADAP MINAT MENABUNG NASABAH DI BANK SYARIAH - RONI ANDESPA (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The research theme is the concept of the bank in accordance with Islamic economics. The purpose of research in this paper is: a) To measure the influence of psychological factors to the variable interest in saving partially, b) To measure the influence of psychological factors to the variable interest in saving partially. The object of research is sharia bank in West Sumatra. This research is quantitative research. The population is all customers of sharia banks in West Sumatra. The sample was 250 people. Data analysis using multiple linear regression analysis. The research variables are psychological factors and interest in saving. There was a significant influence between personal factors on the interest of saving.